1997
DOI: 10.1093/treephys/17.8-9.521
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of branch-level gas exchange of boreal trees: roles of shoot water potential and vapor pressure difference

Abstract: Effects of shoot water potential (Psi) and leaf-to-atmosphere vapor pressure difference (VPD) on gas exchange of jack pine (Pinus banksiana Lamb.), black spruce (Picea mariana (Mill.) B.S.P.), and aspen (Populus tremuloides Michx.) were investigated at the northern edge of the boreal forest in Manitoba, Canada. Laboratory measurements on cut branches showed that net photosynthesis (A(n)) and mesophyll conductance (g(m)) of jack pine and g(m) of black spruce did not respond to Psi until a threshold Psi was reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
2
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(102 citation statements)
references
References 58 publications
9
89
2
2
Order By: Relevance
“…An exponential rise to a maximum is the form commonly used to describe stomatal response to light (Jarvis 1976). Many forms of non-linear functions have been used to describe the decrease in G S with increases in D (see Lohammar et al 1980;Massman and Kaufmann 1991;McNaughton and Jarvis 1991;Granier and Loustau 1994;McCaughey and Iacobelli 1994;Monteith 1995;Dang et al 1997;Martin et al 1997). Models use these functions to generate a multiplier, one of several used in multipleconstraint functions, to reduce maximum g S or G S to estimates of actual conductance (see Schulze et al 1994); maximum conductance is determined for each species under non-limiting environmental conditions (e.g., high irradiance without water limitation; Dai et al 1992).…”
Section: Daytime Responses Of G S To E L Q O and Dmentioning
confidence: 99%
“…An exponential rise to a maximum is the form commonly used to describe stomatal response to light (Jarvis 1976). Many forms of non-linear functions have been used to describe the decrease in G S with increases in D (see Lohammar et al 1980;Massman and Kaufmann 1991;McNaughton and Jarvis 1991;Granier and Loustau 1994;McCaughey and Iacobelli 1994;Monteith 1995;Dang et al 1997;Martin et al 1997). Models use these functions to generate a multiplier, one of several used in multipleconstraint functions, to reduce maximum g S or G S to estimates of actual conductance (see Schulze et al 1994); maximum conductance is determined for each species under non-limiting environmental conditions (e.g., high irradiance without water limitation; Dai et al 1992).…”
Section: Daytime Responses Of G S To E L Q O and Dmentioning
confidence: 99%
“…Photosynthesis peaks when SWC is near the field capacity and decreases with the departure of SWC from this optimum. When soil or atmospheric water is insufficient, leaf stomatal conductance reduces and correspondingly CO 2 fixation is limited (Dang et al, 1997;Hogg et al, 2000;Grant et al, 2006a). Extensive studies have demonstrated the influence of SWC on C fixation at leaf (Infante et al, 1999;Lawlor, 1995) and canopy (Reichstein et al, 2002;Rambal et al, 2003) levels.…”
Section: Introductionmentioning
confidence: 99%
“…But these structures are not available everywhere and there is need for reliable estimates of leaf-level processes in places where it is not practical to build such structures. Researchers have measured gas exchange of canopy leaves by cutting or shooting small branches and re-cutting stems under water to reestablish the xylem water column in the form of a potometer before measurement (Koyama 1981, Reich et al 1995, 1998, Dang et al 1997. Other researchers have measured gas exchange of trees by simply detaching a group of leaves and placing them in a cuvette for immediate measurement (Ginn et al 1991, Gerrish 1992, Samuelson 1998.…”
Section: Introductionmentioning
confidence: 99%
“…The time scale at which these changes occur is likely to be important in determining the degree of excision-induced effects on gas exchange. However, these responses vary widely across the plant kingdom leaving us with little information regarding the reliability of gas exchange measurements on excised foliage; few studies provide verification of how leaves on excised stems perform (Ginn et al 1991, Dang et al 1997.…”
Section: Introductionmentioning
confidence: 99%